Economic Crisis in a Stalemated Democracy: The Italian Case. (November 2014) - Morlino, Leonardo; Piana, Daniela
In Southern Europe, the economic crisis (2008-2013) triggered a deeper political crisis, affecting a number of aspects of a representative democracy. Italy provides a particularly telling case of what happens when an economic crisis occurs in an unstable political context characterized by low government effectiveness, low efficiency, corruption, decline of electoral participation, fragmented and radicalized party competition, social inequality, high public debt, and other related features, here summarized in the model of "stalemated democracy." On the basis of a comprehensive data set developed along with eight dimensions of democracy assessment and taking into account the policies pursued during the years of the crisis, we analyze the different effects of economic crisis—some of them expected, others more surprising—and how those effects characterize Italian political crisis and a new phase of great uncertainty. In the concluding remarks we offer an explanation of the role played by the economic crisis, focusing on the interplay between veto rules and actual veto players. Such an explanation is also relevant to see key, more in-depth aspects of Italian democracy during last 20 years and earlier.